Experimental research on the ash deposition characteristics of 3-D finned tube bundle. (5th May 2019) - Cheng, Min; Chen, Zi-yong; Liao, Qiang; Zhang, Jun-nan; Ding, Yu-dong; Zhu, Xun
Highlights: Ash deposition on 3-D finned tube bundle mostly occurs on the fin surface. Larger particles prefer to settle on the tube surface of top side and leeward side. Smaller particles mainly deposit on the fin surface of windward side and leeward side. Longer transverse tube pitch and shorter longitudinal tube pitch can restrict ash deposition. Ash deposition remits firstly and then intensifies with the increase of fin height. Abstract: Ash deposition on the flue gas side of a heat recovery device can cause significant industrial problems. 3-D finned tube is a new type of heat exchanger element with potential anti-fouling property. However, the ash deposition characteristics of 3-D finned tube bundle are still unclear. In the current study, experiments were conducted to study the ash distribution characteristics of 3-D finned tube bundle with six-tube rows. The effects of the tube bundle structure, including the transverse tube pitch, longitudinal tube pitch and fin height, were investigated on the ash distribution around the tube along with the overall ash deposition weight. The results indicate that ash particles primarily distribute on the fin surface under different arrangements of the 3-D tube bundle. Larger particles prefer to settle on the tube surface of the top side and the leeward side, whereas smaller particles primarily settle on the fin surface of the windward side and the leeward side. The weight measurement results indicate that a longer transverse tube pitch and a shorter longitudinal tube pitch significantly restrict the ash deposition under current operating conditions. The ash deposition first decreases and then intensifies with an increase in fin height from 2 mm to 5 mm. The optimal fin height for anti-fouling is 3 mm.